Stabilizing the Microphase Separation of Block Copolymers by Controlled Photo‐crosslinking. Issue 16 (7th July 2014) - Tietz, Katharina; Finkhäuser, Stefanie; Samwer, Konrad; Vana, Philipp
<x xml:space="preserve">Abstract</x> Photo‐crosslinkable material is produced via self‐assembly of poly(methyl methacrylate)‐block‐poly(n‐butyl acrylate) (PMMA‐b‐PBA) block copolymers, in which the MMA block is decorated with coumarin moieties. The block copolymer is synthesized by reversible addition‐fragmentation chain transfer (RAFT) polymerization. Atomic force microscopy (AFM) reveals microphase separation into nanodomains of controlled and regular morphology. The local elastic modulus of different nanodomains is determined using the PeakForce Quantitative Nano‐Mechanics (PFQNM) mode of AFM. The global modulus, as determined by mechanical spectroscopy, agrees well with the local values. The crosslinking of the block copolymer, via photodimerization of the incorporated coumarin moieties using UV light, is traced by UV–vis absorption measurements and resulted in an increase of the global elastic modulus. The crosslinking reaction proceeding in the solid state is surprisingly effective and stabilizes the morphology to such an extent that equilibrium phase separation, as targeted by annealing, is effectively suppressed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>